2nd International Conference on Islamic Economics and Economies of the OIC Countries (ICIE 2013) - Kayadibi, Saim (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2013)
The 2nd International Conference on Islamic Economics and Economies of the OIC countries (ICIE 2013) was convened in Kuala Lumpur, 29-30 January 2013. It was jointly organised by the Department of Economics (College of Economics and Management Sciences) of the International Islamic University Malaysia (IIUM), the Malaysian Ministry of Finance and the Islamic Research and Training Institute (IRTI), with the collaboration of two universities: University of Medeniyet, Turkey, and Bogor Agricultural University, Indonesia, as partners. A total of 33 different countries participated. The two keynote speakers, Savaş Alpay (Director General of Statistical Economic Social Research and Training Centre for Islamic Countries [SESRIC]), and Monzer Kahf (Laureate of Islamic Development Bank [IDB] Prize in Islamic Economics), were joined by the Second Finance Minister of Malaysia, Ahmad Husni Mohamad Hanadzlah, and public and government representatives and international academics, in the presentation of ninety-two (92) different papers on diverse themes.